Validation of the Thai Version of a Work-related Quality of Life Scale in the Nursing Profession - Poramate Sirisawasd; Naesinee Chaiear; Nutjaree Pratheepawanit Johns; Jiraporn Khiewyoo (Elsevier, 2014)
Background: Currently available questionnaires for evaluating the quality of worklife do not fully examine every factor related to worklife in all cultures. A tool in Thai is therefore needed for the direct evaluation of the quality of worklife. Our aim was to translate the Work-related Quality of Life Scale-2 (WRQLS-2) into Thai, to assess the validity and reliability of the Thai-translated version, and to examine the tool's accuracy vis-à-vis nursing in Thailand. Methods: This was a descriptive correlation study. Forward and backward translations were performed to develop a Thai version of the WRQLS. Six nursing experts participated in assessing content validity and 374 registered nurses (RNs) participated in its testing. After a 2-week interval, 67 RNs were retested. Structural validity was examined using principal components analysis. The Cronbach's alpha values were calculated. The respective independent sample t test and intraclass correlation coefficient were used to analyze known-group validity and test-retest reliability. Multistate sampling was used to select 374 RNs from the In- and Outpatient Department of Srinagarind Hospital of the Khon Kaen University (Khon Kaen, Thailand). Results: The content validity index of the scale was 0.97. Principal components analysis resulted in a seven-factor model, which explains 59% of the total variance. The overall Cronbach's alpha value was 0.925, whereas the subscales ranged between 0.67 and 0.82. In the assessment results, the known-group validity was established for the difference between civil servants and university employees [F (7.982, 0.005) and t (3.351; p < 0.05)]. Civil servants apparently had a better quality worklife, compared to university employees. Good test-retest reliability was observed (r = 0.892, p < 0.05). Conclusion: The Thai version of a WRQLS appears to be well validated and practicable for determining the quality of the work-life among nurses in Thailand.